"From a sweet-smelling mouth to a well-tuned ear" : Testimony on the Diffusion of the Repertory of a Zarma "Jasare" in Niger - (:unkn) unknown (My University, 2007)
Based on an account of a meeting between a young Western researcher and a Zarma "jasare" (a griot of history and genealogy) of Niger, this article explores the problems connected with the collection, preservation and diffusion of oral literature. This is, obviously, a peculiar case, but it is illustrative enough to be invoked. Indeed, with the evolution of Zarma society, the training of the "jasare" has gradually declined so that today there is barely one left who knows the story of the incestors : Jibo Baje, alias "Jeliba". Aware that he is the last depository of the oral literature of the "jasare" and that none of his sons would replace him, he has entrusted the author with the mission of preserving and passing on his repertory to other cultures.
Keywords: African Research